Do investors become risk takers after receiving MLA and accounting information? - Ni Made Wisni Arie Pramuki; Bambang Subroto; Imam Subekti (Universitas Hayam Wuruk Perbanas, 2016)
This study aimed to find out, empirically, the effect of myopic loss aversion and accounting information on the behavior of investors. The method used is pure experiment by using a 2Ã—2 factorial design between subjects. The results show that myopic loss aversion and accounting information positively affects investor behavior. Another result reveals that there is a difference in treatment (frequent and infrequent) that was equally given accounting information. There is a difference of treatment (frequent and infrequent) that was not given accounting information, but the results return obtained by investors with the treatment of frequent is higher than investors with the treatment of infrequent, it indicates that investors that were treated frequently to be more willing to take a risk, and investors proved not to experience MLA. It was not found the difference in treatment (frequent and infrequent) with accounting information with those that were not given accounting information. It can be caused by a lack of understanding of investors (in this case by the students) in interpreting and analyzing accounting information as well as private signals that still dominate the investors.